Experimental studies on the efficacy of artesunate and oxytetracycline combination against induced BTT in crossbred calves - PATEL, DINESH; MISRAULIA, K S; REDDY, A GOPALA; GARG, U K; SHARMA, R K; GUPTA, BRAJESH KUMAR (The Indian Journal of Animal Sciences, 2014)
The efficacy of artesunate in combination with oxytetracycline was assessed in order to evolve an alternative to standard chemotherapeutic agents against bovine/tropical theileriosis (BIT). Experimental induction of BIT in 12 crossbred male calves with ground up tick supernates prepared from Hyalomma anatolicum anatolicum infected with Theileria annulata resulted in significant (P< 0.01) decrease in TEC, TLC, Hb, PCV, MCHC, total protein and total serum albumin, and significant (P